A longitudinal study of working hours and chronic kidney disease in healthy workers: The Kangbuk Samsung Health Study. Issue 1 (11th August 2021) - Lee, Yesung; Seo, Eunhye; Mun, Eunchan; Lee, Woncheol
Abstract: Objectives: Long working hours are linked to an increased risk of exposure to work safety hazards that threaten the health of workers. To date, only a few cross‐sectional studies regarding the relationship between working characteristics, such as over‐workload and chronic kidney disease (CKD) have been reported. Therefore, in this longitudinal study, we aimed to examine the direct relationship between long working hours and the incidence of CKD. Methods: We included 97 856 participants without CKD in the Kangbuk Samsung Health Study. Using a self‐report questionnaire, we evaluated weekly working hours, which were categorized into 35‐40, 41‐52, and >52 hours. CKD was defined as estimated glomerular filtration rate <60 mL/min/1.73 m 2 . Hazard ratios (HRs) and 95% confidence intervals (CIs) for incident CKD were estimated using Cox proportional hazards regression analyses with weekly working 35‐40 hours as the reference. Results: During a median follow‐up of 4.0 years, 185 participants developed incident CKD (incidence density, 4.83 per 10 4 person‐years). Multivariable‐adjusted HRs (95% CI) of incident CKD for weekly working >52 hours compared with working 35‐40 hours were 1.99 (1.22‐3.25). In subgroup analyses, the significant association between working >52 hours and incident CKD was consistently observed in groups of age ≥40 years, men, and obesity with no interaction. Conclusions: Our large‐scale cohort study of young‐ to middle‐aged men and women demonstrated a significant association between long working hours and an increased risk of incident CKD.